Interventions to promote physical activity for adults with intellectual disabilities - Viviene A Temple; Georgia C Frey; Heidi I Stanish (Instituto Nacional de Salud Pública, 2017)
Objective. To describe interventions designed to promote physical activity for adults with intellectual disabilities and the effects on overall physical activity levels and on health outcomes. Materials and methods. A systematic review of eight databases until January 31, 2015 identified 383 citations. The inclusion criteria were: a) the study sample consisted of adults with intellectual disabilities, b) the study implemented an intervention to initiate, increase, or maintain physical activity, and c) quantitative or qualitative data were used to report the effectiveness of the intervention. Six articles from the 383 citations met this criterion. Results. Three studies resulted in significant increases in physical activity behaviour; however well-controlled trials designed to improve weight status by increasing physical activity did not produce significant effects. Conclusion. Overall, the results indicate that interventions to increase physical activity should simultaneously target the individual with intellectual disability as well as their proximal environment over a sustained period of time.